Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPS dengan Menggunakan Model Pembelajaran PjBL (Project Based Learning) pada Siswa Kelas V SDN 187/I Teratai - Azilla, Marsya Deva; Nurlaiala, Putri; Juita, Roja; Rezani, Regita Mutiara (TSAQOFAH, 2023)
IPS should be a lesson that is liked by students at school. The aim of this study was to increase student motivation in social studies subjects using the Project Based Learning learning model in class V SD 187/I Teratai. This type of research is classroom action research with 10 students, consisting of 5 male students and 5 female students. This research was conducted in semester I of the 2022/2023 Academic Year. The schedule for conducting research in August-September 2022. Data collection techniques include observation, interviews, tests and discussions. This research model has four components, namely planning, action, observation, and reflection. The research was conducted in 2 cycles, each cycle held 2 meetings. The results of this study indicate that using the Project Based Learning learning model can increase student learning motivation in social studies learning. This means that the Project Based Learning learning model can be used by teachers as a good model to be applied in the learning process so that it can achieve the desired goals. and can create a fun learning atmosphere for students.